D2/3 Agonist during Learning Potentiates Cued Risky Choice - Mortazavi, Leili; Hynes, Tristan J; Chernoff, Chloe S; Ramaiah, Shrishti; Brodie, Hannah G; Russell, Brittney; Hathaway, Brett A; Kaur, Sukhbir; Winstanley, Catharine A (The Journal of neuroscience, 2023)
Impulse control and/or gambling disorders can be triggered by dopamine agonist therapies used to treat Parkinson's disease, but the cognitive and neurobiological mechanisms underlying these adverse effects are unknown. Recent data show that adding win-paired sound and light cues to the rat gambling task (rGT) potentiates risky decision-making and impulsivity via the dopamine system, and that changing dopaminergic tone has a greater influence on behavior while subjects are learning task contingencies. Dopamine agonist therapy may therefore be potentiating risk-taking by amplifying the behavioral impact of gambling-related cues on novel behavior. Here, we show that ropinirole treatment in male rats transiently increased motor impulsivity but robustly and progressively increased choice of the high-risk/high-reward options when administered during acquisition of the cued but not uncued rGT. Early in training, ropinirole increased win-stay behavior after large unlikely wins on the cued rGT, indicative of enhanced model-free learning, which mediated the drug's effect on later risk preference. Ex vivo cFos imaging showed that both chronic ropinirole and the addition of win-paired cues suppressed the activity of dopaminergic midbrain neurons. The ratio of midbrain:prefrontal cFos+ neurons was lower in animals with suboptimal choice patterns and tended to predict risk preference across all rats. Network analyses further suggested that ropinirole induced decoupling of the dopaminergic cells of the VTA and nucleus accumbens but only when win-paired cues were present. Frontostriatal activity uninformed by the endogenous dopaminergic teaching signal therefore appeared to perpetuate risky choice, and ropinirole exaggerated this disconnect in synergy with reward-paired cues.